2003
DOI: 10.1289/ehp.6251
|View full text |Cite
|
Sign up to set email alerts
|

Association between gaseous ambient air pollutants and adverse pregnancy outcomes in Vancouver, Canada.

Abstract: The association between ambient air pollution and adverse health effects, such as emergency room visits, hospitalizations, and mortality from respiratory and cardiovascular diseases, has been studied extensively in many countries, including Canada. Recently, studies conducted in China, the Czech Republic, and the United States have related ambient air pollution to adverse pregnancy outcomes. In this study, we examined association between preterm birth, low birth weight, and intrauterine growth retardation (IUG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
256
9
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(295 citation statements)
references
References 50 publications
19
256
9
11
Order By: Relevance
“…Similar associations between air pollution and fetal growth restrictions were observed for maternal exposures estimated either by month or by trimester of pregnancy. The present findings are consistent with those in our previous report on the association between gaseous air pollutants and IUGR based on data from Vancouver (Liu et al, 2003), as well as those in studies conducted by other investigators (Dejmek et al, 1999;Bobak, 2000;Maroziene and Grazuleviciene, 2002;Parker et al, 2005).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Similar associations between air pollution and fetal growth restrictions were observed for maternal exposures estimated either by month or by trimester of pregnancy. The present findings are consistent with those in our previous report on the association between gaseous air pollutants and IUGR based on data from Vancouver (Liu et al, 2003), as well as those in studies conducted by other investigators (Dejmek et al, 1999;Bobak, 2000;Maroziene and Grazuleviciene, 2002;Parker et al, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…An IUGR birth is defined as an infant whose birth weight falls below the 10th percentile, by sex and gestational week, of all singleton live births in Canada between 1986 and 2000 (Kramer, 2003;Liu et al, 2003). All singleton live births at 37-42 weeks of gestation were included in this study.…”
Section: Live Births and Iugrmentioning
confidence: 99%
See 1 more Smart Citation
“…Low levels of air pollution affect early stages of human development as well. Liu et al [19] found low ambient air pollution concentrations associated with adverse pregnancy outcomes (low birth weight, preterm birth, and intrauterine growth retardation). Not only is air pollution associated with increased mortality and morbidity, it is also linked to an increase in the number of hospital admissions (Burnett et al, [12,20]; Linn et al, [21]; Peters et al [22]; Oftedal et al [23]).…”
Section: Introductionmentioning
confidence: 99%
“…Em sua maioria são estudos epidemiológicos que indicam uma associação da exposição parenteral à poluição do ar nos grandes centros urbanos com desfechos negativos como o baixo peso do recém nascido, mortalidade neonatal, prematuridade e restrição no crescimento intrauterino (Holstius et al, 2012;Chang et al, 2012;;Liu et al, 2003;Maisonet et al, 2001;Gauderman et al, 2000;Wang et al, 1997 (Croy, Kiso, 1993;Croy et al, 2006;Taront et al, 2009).…”
Section: Introductionunclassified